2019
DOI: 10.1128/jvi.00569-19
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effects of Immunoproteasome Deficiency on Mouse Adenovirus Type 1 Pathogenesis

Abstract: Acute respiratory infection with mouse adenovirus type 1 (MAV-1) induces activity of the immunoproteasome, an inducible form of the proteasome that shapes CD8 T cell responses by enhancing peptide presentation by major histocompatibility complex (MHC) class I. We used mice deficient in all three immunoproteasome subunits (triple-knockout [TKO] mice) to determine whether immunoproteasome activity is essential for control of MAV-1 replication or inflammatory responses to acute infection. Complete immunoproteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Notably, using the LCMV infection model, Nussbaum et al, observed that although LMP2 -/or LMP7 -/mice had fewer CD8 + T cells, these animals were able to mount strong CD8 + anti-viral immune responses demonstrated by similar kinetics of viral clearance compared to WT mice (57). In addition, analyzing the role of mouse adenovirus type 1 infection in pathogenesis of TKO mice the authors detected age-dependent differing effects (58). All these studies demonstrate that the role of the IP during infection is multifaceted and most likely pathogen specific.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, using the LCMV infection model, Nussbaum et al, observed that although LMP2 -/or LMP7 -/mice had fewer CD8 + T cells, these animals were able to mount strong CD8 + anti-viral immune responses demonstrated by similar kinetics of viral clearance compared to WT mice (57). In addition, analyzing the role of mouse adenovirus type 1 infection in pathogenesis of TKO mice the authors detected age-dependent differing effects (58). All these studies demonstrate that the role of the IP during infection is multifaceted and most likely pathogen specific.…”
Section: Discussionmentioning
confidence: 99%
“…MAdV‐1 also causes myocarditis that is accompanied by myocyte and endothelial necrosis when inoculated intraperitoneally or intranasally . Many mouse primary cell types, cell strains, and established cell lines can support MAdV‐1 replication in vitro , including fibroblasts (3T6, 3T12 and L929) , endothelial cells (MBMEC) , preadipocyte cells (3T3‐L1) , epithelial cells (LA‐4, MLE‐12 and MLE‐15; J.B. Weinberg, unpublished), cardiac myocytes macrophages/monocytes , and tumor cells such as lung adenoma (LA‐4), renal adenocarcinoma (RAG) , and rectal carcinoma (CMT‐93) cells .…”
Section: Madv‐1 Pathogenesis—tropism Adaptive Immune Responsesmentioning
confidence: 99%
“…Intranasal inoculation of MAdV‐1 results in significantly increased immunoproteasome activity in the lung and heart compared to uninfected mice , and this is dependent on IFNγ. The immunoproteasome is important for survival of neonatal mice infected with MAdV‐1 .…”
Section: Madv‐1 Pathogenesis—innate Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike CVB3 however, many HAdVs cannot replicate effectively in mice, resulting in a dearth of understanding regarding adenoviral cardiotropism and virus-specific effects on the heart due to this stringent adenoviral speciesspecificity 46,54 . Mouse adenovirus type 1 (MAdV-1) has historically been employed in modeling respiratory disease and encephalitis, and while not a 'cardiotropic' virus, additional studies have successfully modeled adenoviral myocarditis in mice using MAdV-1, with an emphasis on inflammation [55][56][57][58] . In 2008, mouse adenovirus type-3 (MAdV-3) was isolated as distinct from the previously described MAdV-1 and MAdV-2, and reported to be cardiotropic 59,60 .…”
Section: Introductionmentioning
confidence: 99%